2015
DOI: 10.1158/0008-5472.can-15-0988
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastomas Require Integrin αvβ3/PAK4 Signaling to Escape Senescence

Abstract: Integrin αvβ3 has been implicated as a driver of aggressive and metastatic disease, and is upregulated during glioblastoma progression. Here we demonstrate that integrin αvβ3 allows glioblastoma cells to counteract senescence through a novel tissue-specific effector mechanism involving recruitment and activation of the cytoskeletal regulatory kinase PAK4. Mechanistically, targeting either αvβ3 or PAK4 led to emergence of a p21-dependent, p53-independent cell senescence phenotype. Notably, glioblastoma cells di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
2
29
0
1
Order By: Relevance
“…Further, human breast cancer cells harboring stable PAK4 knockdown grew slower when injected subcutaneously onto the back of immunodeficient mice and formed smaller tumors that were highly positive for SA-β-galactosidase activity. 1 We could thus show that several epithelial cancers are susceptible to arrest upon PAK4 inhibition, as suggested for glioblastomas 10 further supporting the notion of generalized PAK4 addiction in cancer. 5 Guided by transcriptome analyzes, mass spectrometry and computational modeling, we also identified a new PAK4mediated signaling pathway that controls senescence in breast cancer (Figure 1(b)).…”
supporting
confidence: 74%
“…Further, human breast cancer cells harboring stable PAK4 knockdown grew slower when injected subcutaneously onto the back of immunodeficient mice and formed smaller tumors that were highly positive for SA-β-galactosidase activity. 1 We could thus show that several epithelial cancers are susceptible to arrest upon PAK4 inhibition, as suggested for glioblastomas 10 further supporting the notion of generalized PAK4 addiction in cancer. 5 Guided by transcriptome analyzes, mass spectrometry and computational modeling, we also identified a new PAK4mediated signaling pathway that controls senescence in breast cancer (Figure 1(b)).…”
supporting
confidence: 74%
“…We previously reported that knockdown of β3 induced a senescent phenotype in GBM cells (Franovic et al, 2015). Here we show that Glut3 knockdown also induces multiple markers of senescence in vitro, including β-galactosidase (SA-β-gal) activity, G0/G1 cell cycle arrest, and γH2AX (Figures 2I–2J and S2C–S2E).…”
Section: Resultsmentioning
confidence: 99%
“…Since we recently implicated PAK4 as a mediator of β3 function (Franovic et al, 2015), we considered whether this kinase may also be required for β3-mediated regulation of YAP/TAZ expression. Indeed, inhibition of PAK4 activity using the PAK4 kinase inhibitor PF-03758309 or knockdown of PAK4 expression using shRNA led to a decrease of YAP/TAZ (and Glut3) expression (Figures S3C–S3F and 3H).…”
Section: Resultsmentioning
confidence: 99%
“…αvβ5 inhibition has possible pro-tumourigenic properties in both HNSCC [44,59,60] and glioblastoma [77], thus a combination αvβ3/αvβ5 targeting agent may be self-defeating in these cancers. Tumour expression of related integrins not effectively inhibited by cilengitide may also provide a mechanism for drug resistance and therapeutic failure.…”
Section: Integrins In Hnsccmentioning
confidence: 99%